Correlation between heart rate variability and myocardial perfusion scintigraphy. Issue 4 (2018) - Raimundo, Rodrigo Daminello; Santoro, Patricia Alves Ribeiro; Santos, Pamela de Souza; Santoro, Victor; Valenti, Vitor Engrácia; Carvalho, Tatiana Dias de; Pérez-Riera, Andrés Ricardo; Raimundo, Juliana Zangirolami; Andrade, Paulo Evaristo de; Abreu, Luiz Carlos de
No abstract available